From Application of Socio-Scientific Issues in Chemistry Learning to Improve Science Literacy and Awareness Student Social - Pangaribuan, Devy J.R; Daulay, Rabiah Afifah; Manik, Lia Yustina; Panjaitan, Khayla Akmal; Siagian, Andin Livia; Lumban Gaol, Sri Rosa (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The Socio-Scientific Issues (SSI) approach is a learning strategy based on social issues related to science, which aims to improve students' scientific literacy and critical thinking skills. And this approach is able to improve students' scientific literacy and social awareness by connecting chemical concepts to real-world social challenges. This literature review examines the effectiveness of SSI-based learning in improving critical thinking, argumentation skills, and contextual understanding among students. The research method used is a literature review using 10 journals as findings showing that SSI encourages deeper engagement by connecting chemistry to issues such as environmental pollution, industrial waste, and sustainable development, making learning more relevant and meaningful. However, challenges such as limited teacher familiarity with SSI integration, curriculum constraints, and students' difficulties in analyzing complex socio- scientific debates hinder its widespread implementation. Proposed solutions include teacher training programs, adoption of problem-based and inquiry-based learning models, and institutional support for curriculum development. The study concludes that SSI significantly improves scientific literacy and decision-making skills when supported by structured pedagogical strategies and institutional commitment. Future research should focus on a scalable SSI implementation framework and its long-term impact on students' social and scientific competencies.